Genome sequence of carbapenem-resistant Citrobacter koseri carrying blaOXA-181 isolated from sewage sludge - Mutshiene Deogratias Ekwanzala; John Barr Dewar; Ilunga Kamika; Maggy Ndombo Benteke Momba (Journal of Global Antimicrobial Resistance, 2020)
Objectives: This study reported the resistome content of sewage sludge-isolated carbapenem-resistant Citrobacter koseri (C. koseri) carrying blaOXA-181. It also provided a general phylogenomic analysis highlighting antibiotic resistance genes (ARGs), plasmids and pathogenicity of C. koseri genomes. Methods: The carbapenem-resistantC. koseri AS1 strain was isolated from sewage sludge on CHROMagar™ mSuperCARBA™ media. Whole genome sequencing of C. koseri AS1 was performed using an HiSeq X™ Ten instrument. Additional C. koseri genomes were downloaded from National Center for Biotechnology Information (NCBI). Phylogenomic analysis was established through CSI Phylogeny. ARGs, plasmids and pathogenicity were identified using ResFinder 3.1, PlasmidFinder 2.0 and PathogenFinder 1.1, respectively. Results: The phylogenomic tree indicated a polyclonal pattern ofC. koseri genomes. Resistome analysis of C. koseri AS1 revealed β-lactam resistance genes (blaMAL-1 and blaOXA-181) as well as a fosfomycin resistance gene (fosA7). Three plasmids (ColKP3, ColRNAI and IncX30) were identiﬁed in the C. koseri AS1 genome. In addition, 25 ARGs were found in downloaded genomes. Of these, clinically significant ARGs such as blaKPC-2 and blaOXA-48 were found in two and four genomes, respectively. Assessment of the genomes using PathogenFinder revealed all genomes as putative human pathogens. Conclusions: It is believed that noC. koseri genome has been reported to carry blaOXA-181; therefore, C. koseri AS1 is the first of its kind. This study also highlighted the resistome contents of C. koseri genomes.